Heterorhabditis, Steinernema and their bacterial symbionts — lethal pathogens of insects - Burnell, Ann; Stock, S. Patricia (Nematology : international journal of fundamental and applied nematological research, 2000)
AbstractThe entomopathogenic nematodes (EPN) Heterorhabditis and Steinernema together with their symbiont bacteria Photorhabdus and Xenorhabdus, respectively, are obligate and lethal parasites of insects. EPN can provide effective biological control of some important lepidopteran, dipteran and coleopteran pests of commercial crops and they are amenable to large-scale culture in liquid fermentors. They are unique among rhabditids in having a symbiotic relationship with an enteric bacterium species. The bacterial symbiont is required to kill the insect host and to digest the host tissues, thereby providing suitable nutrient conditions for nematode growth and development. This review describes the general biology of EPN and their symbionts and gives an overview of studies to date on EPN biodiversity, biogeography and phylogeny. The impetus for research in EPN and their symbionts has come about because of their biological control potential, with much of the focus in EPN research having been on applied aspects relating to pest control. However EPN and their symbionts are increasingly being viewed as exciting subjects for basic research in the areas of ecology, biodiversity, evolution, biochemistry, symbiosis and molecular genetics. Much progress has been made over the past 20 years in our understanding of the basic biology and genetics of EPN and their symbionts. We are now entering a new phase in which the tools of molecular genetics are being increasingly used to address a range of biological questions in EPN research. The knowledge gained from this endeavour should ensure that EPN will become even more effective biopesticides and should also ensure that EPN and their symbionts gain prominence as unique and intrinsically interesting biological systems. Les nématodes entomopathogènes (EPN) Heterorhabditis et Steinernema, avec leur bactéries symbiotes Photorhabdus et Xenorhabdus, respectivement, sont des parasites obligés et mortels des insectes. Les EPN peuvent servir à un contrôle biologique de quelques lépidoptères, diptères et coléoptères importants pour les cultures commerciales et ils sont élevables à grande échelle dans des fermenteurs liquides. Ils sont uniques chez les rhabditides par leur relation symbiotique avec une espèce de bactérie entérique. La bactérie symbiote est nécessaire pour tuer l’insecte hôte et pour digérer les tissus de l’hôte, permettant ainsi des conditons de nutrition favorables à la croissance et au développement du nématode. La présente revue décrit la biologie générale des EPN et de leur symbiotes et donne un état des études actuelles sur la biodiversité, la biogéographie et la phylogénie des EPN. L’impulsion donnée aux recherches sur les EPN et leur symbiotes provient de leur potentialités pour le contrôle biologique, une grande partie des recherches sur les EPN ayant trait à des aspects appliqués en relation avec ce contrôle des parasites. Cependant, les EPN et leur symbiotes bactériens sont de plus en plus considérés comme des sujets intéressants pour la recherche fondamentale dans les domaines de l’écologie, de la biodiversité, de l’évolution, de la biochimie, des processus symbiotiques et de la génétique moléculaire. De nombreux progrès ont été réalisés ces 20 dernières années dans la compréhension de la biologie et de la génétique des EPN et de leur symbiotes. Nous entrons actuellement dans une nouvelle phase ou les moyens de la biologie moléculaire sont utilisés de manière croissante pour formuler une série de questions biologiques pour la recherche sur les EPN. Les connaissances résultant de ces efforts doivent conduire à vérifier que les EPN deviendront des biopesticides toujours plus efficaces et que les EPN et leur symbiotes prendront de l’importance en tant que systèmes biologiques uniques et intrinsèquement intéressants.